2016
DOI: 10.2147/nss.s104383
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific sleep patterns among university students in Lebanon: impact on depression and academic performance

Abstract: Good sleep quality and quantity are fundamental to the maintenance of normal physiological processes. Changes in sleep patterns are commonly observed among young adults and are shown to impact neurocognitive, academic, and psychological well-being. Given the scarcity of sleep information about Lebanon and acknowledging the sex differences in various sleep dimensions, we conducted a study that aimed at assessing sex differences in sleep habits among university students in Lebanon in relation to psychoacademic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…This study reveals that 20% of the university students in Lebanon are suffering from anxiety or/and depression which is similar to the previous reports in Lebanon that showed 24.2% of university students are categorized as mild-to-moderately depressed (Kabrita & Hajjar-Muca, 2016). This percentage is alarming not only in Lebanon but in similar context such as Jordan that has high unemployment rates, high number of Syrian refugees, and cultural and religious restrictions (Dalky & Gharaibeh, 2019).…”
Section: Analysis Of the Relation Between Life Skills And Mentalsupporting
confidence: 90%
“…This study reveals that 20% of the university students in Lebanon are suffering from anxiety or/and depression which is similar to the previous reports in Lebanon that showed 24.2% of university students are categorized as mild-to-moderately depressed (Kabrita & Hajjar-Muca, 2016). This percentage is alarming not only in Lebanon but in similar context such as Jordan that has high unemployment rates, high number of Syrian refugees, and cultural and religious restrictions (Dalky & Gharaibeh, 2019).…”
Section: Analysis Of the Relation Between Life Skills And Mentalsupporting
confidence: 90%
“…It has been reported that as high as 33-59% of university students have poor sleep quality, which is associated with their worsened health status and academic performance [5,[13][14][15][16][17][18][19]. In these previous studies, sleep quality was defined as "poor" or "good" using the Pittsburg Sleep Quality Index (PSQI), a widely used scale evaluating the following seven components: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio for men and women developing insomnia symptoms is increasing with age [7]. According to Kabrita et al [8] and Tsai et al [9], women reported significant earlier bedtime and rise time, longer sleep-onset latency, more awakenings, and poorer sleep quality based on subjective sleep measures (sleep log), whereas objective sleep measures (polysomnography) showed a better sleep quality, longer sleep duration, shorter sleep-onset latency, and higher sleep efficiency in women compared with men [10]. Research also stated that sleep is essential for an efficient consolidation of knowledge and skills [11].…”
Section: Introductionmentioning
confidence: 99%